2020
DOI: 10.1038/s41598-020-67956-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a unique temporal signature in blood and BAL associated with IPF progression

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive and heterogeneous interstitial lung disease of unknown origin with a low survival rate. There are few treatment options available due to the fact that mechanisms underlying disease progression are not well understood, likely because they arise from dysregulation of complex signaling networks spanning multiple tissue compartments. To better characterize these networks, we used systems-focused data-driven modeling approaches to identify cross-tissue compartmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Furthermore, the stable IPF patients survived longer than those with a rapid disease progression [ 16 ]. In an IPF cluster analysis, progressive patients were divided into three different clusters based on three unique expression patterns of proteins, which were pondered to refer different progressive profiles [ 17 ]. In addition, among patients with non-IPF ILDs the survival was shorter in patients with disease progression than in patients with a stable disease course [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the stable IPF patients survived longer than those with a rapid disease progression [ 16 ]. In an IPF cluster analysis, progressive patients were divided into three different clusters based on three unique expression patterns of proteins, which were pondered to refer different progressive profiles [ 17 ]. In addition, among patients with non-IPF ILDs the survival was shorter in patients with disease progression than in patients with a stable disease course [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with IPF have been shown to have a unique peripheral blood proteome [ 3 , 4 ]. Furthermore, a recent report suggested that the circulating proteome may differentiate patients with IPF who will experience progression over the following 80 weeks from those who will remain stable over this period [ 5 ]. We examined the associations between circulating proteins and respiratory death or lung transplant, and the variable importance of circulating proteins as predictors of this outcome, in a cohort of patients from the IPF-PRO Registry.…”
Section: Introductionmentioning
confidence: 99%
“…Airway biomarkers of near-term FVC function decline are also limited, but BAL interferon gamma and transforming growth factor beta may predict progressive RA-ILD ( 193 ). Norman et al recently showed that a BAL fluid proteomic signature may predict near-term IPF progression, with high concentrations of immune-regulatory proteins being associated with slower progression ( 194 ).…”
Section: Airway Biomarkersmentioning
confidence: 99%